ADAM17 as a promising therapeutic target: from structural basis to inhibitor discovery in human diseases - Liu, Lisa; Tian, Erkang; Quan, Shuqi; Su, Chongying; Zhou, Jiawei; Hu, Sijia; Bian, Nanyan; Du, Shufang; Li, Juan (Frontiers in Pharmacology, 2025)
A disintegrin and metalloproteinase 17 (ADAM17) is a transmembrane protease that regulates diverse physiological processes by shedding membrane-bound proteins, including cytokines, their receptors, and adhesion molecules. A mounting body of evidence has emerged linking ADAM17 to the pathogenesis of various diseases, including inflammation, cancer, cardiovascular and neurodegenerative diseases, highlighting its potential as a therapeutic target. This review offers a comprehensive overview of the molecular structure and biological functions of ADAM17, emphasizing its role in human diseases and therapeutic strategies that target ADAM17 activity. Recent advances in the development of ADAM17-targeting agents, including small-molecule inhibitors, monoclonal antibodies, and endogenous regulatory proteins, are discussed with a focus on the structural basis of their activity, with the aim of informing and guiding future drug discovery efforts.